Study of gas-sheared liquid film in horizontal rectangular duct using high-speed LIF technique: three-dimensional wavy structure and its relation to liquid entrainment - Cherdantsev, Andrey V.; Hann, David B.; Azzopardi, Barry J. (Elsevier, 2014)
The flow of a liquid film sheared by high velocity gas stream in a horizontal rectangular duct was investigated using a high-speed laser-induced fluorescence technique. Measurements of local film thickness were resolved in both longitudinal and transverse coordinates with high spatial and temporal resolution. It was found that the generation of fast and slow ripples by the disturbance waves was qualitatively the same as it was observed earlier in completely different conditions. The transverse size and curvature of the disturbance waves and ripples were measured. A relationship between the three-dimensional structure of ripples on top of disturbance waves and the two mechanisms of liquid entrainment, known as ‘bag break-up’ and ‘ligament break-up’, is proposed.